The Relationship Between the Ratio of Independent Commissioners and ESG Performance in Indonesia - Chamelia Gunawan; Cynthia Afriani Utama (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study, titled “The Relationship Between the Ratio of Independent Commissioners and ESG Performance in Indonesia,” examines the potential bidirectional causal relationship between board independence and Environmental, Social, and Governance (ESG) performance among companies in Indonesia. Employing a quantitative approach, the study applies statistical analysis to test the influence of independent commissioners on ESG performance and vice versa. The research controls for variables such as firm size, ownership structure, and IPO year to isolate the effect of board independence on ESG outcomes. Preliminary results indicate that companies with a higher ratio of independent commissioners tend to demonstrate stronger ESG performance. Conversely, companies with better ESG ratings are more likely to attract or retain more independent board structures. This bidirectional causality highlights the importance of strong corporate governance in promoting sustainable business practices. These findings offer practical recommendations for companies and regulators to enhance ESG transparency and accountability through improved board governance structures. Overall, this study underscores the symbiotic relationship between board independence and ESG performance, suggesting that enhanced governance can lead to better sustainability outcomes and vice versa.